Core members and differential abundance of chrysomelid microbiota in the life stages of Podontia affinis (Galerucinae) and adult Silana farinosa (Cassidinae, Coleoptera) - Sze-Looi Song; Hoi-Sen Yong; Kah-Ooi Chua; Praphathip Eamsobhana; Phaik-Eem Lim; Kok-Gan Chan (Biodiversity Data Journal, 2022)
The chrysomelid beetles Podontia affinis and Silana farinosa are members of the subfamilies Galerucinae and Cassidinae, respectively. This study, based on 16S rRNA gene-targeted metagenomics sequencing, reports the core members and differential abundance of bacterial communities in the larvae and adult beetles of P. affinis and the adult S. farinosa. Cyanobacteria/Melainabacteria group was the predominant phylum in the larvae of P. affinis, while Proteobacteria was the predominant phylum in adult P. affinis and S. farinosa. The number of Order, Family, Genus and Species OTUs in the adult stage of P. affinis was higher than that in the larval stage. The bacterial species richness of adult P. affinis was significantly higher than that of adult S. farinosa. Betaproteobacteria was the predominant class in adult P. affinis, Cyanobacteria in the larvae of P. affinis and Gammaproteobacteria in S. farinosa. The larvae and adult beetles of P. affinis and adult S. farinosa had a low number of unique and shared bacterial OTUs (> 5% relative abundance). The differences in the microbiota indicate possible differences in nutrient assimilation, host taxonomy and other stochastic processes. These findings provide new information to our understanding of the bacteria associated with specialist phytophagous chrysomelid beetles and beetles in general.